Strain Sensing Coatings for Large Composite Structures Based on 2D MXene Nanoparticles - Gediminas Monastyreckis; Anastasiia Stepura; Yaryna Soyka; Hanna Maltanava; Sergey K. Poznyak; Mária Omastová; Andrey Aniskevich; Daiva Zeleniakiene (Sensors, 2021)
Real-time strain monitoring of large composite structures such as wind turbine blades requires scalable, easily processable and lightweight sensors. In this study, a new type of strain-sensing coating based on 2D MXene nanoparticles was developed. A Ti3C2Tz MXene was prepared from Ti3AlC2 MAX phase using hydrochloric acid and lithium fluoride etching. Epoxy and glass fibre–reinforced composites were spray-coated using an MXene water solution. The morphology of the MXenes and the roughness of the substrate were characterised using optical microscopy and scanning electron microscopy. MXene coatings were first investigated under various ambient conditions. The coating experienced no significant change in electrical resistance due to temperature variation but was responsive to the 301–365 nm UV spectrum. In addition, the coating adhesion properties, electrical resistance stability over time and sensitivity to roughness were also analysed in this study. The electromechanical response of the MXene coating was investigated under tensile loading and cyclic loading conditions. The gauge factor at a strain of 4% was 10.88. After 21,650 loading cycles, the MXene coating experienced a 16.25% increase in permanent resistance, but the response to loading was more stable. This work provides novel findings on electrical resistance sensitivity to roughness and electromechanical behaviour under cyclic loading, necessary for further development of MXene-based nanocoatings. The advantages of MXene coatings for large composite structures are processability, scalability, lightweight and adhesion properties.